Preparation method of copper-nickel-silver composite metal catalyst and application of copper-nickel-silver composite metal catalyst in preparation of ethanediamine and coproduction of piperazine by catalytic ammoniation of ethylene glycol
By doping metal silver on the alumina support, the problems of low conversion rate and many by-products in the prior art are solved, and the effect of efficient preparation of ethylenediamine and piperazine is achieved, which is suitable for the preparation of ethylenediamine and piperazine. Industrial use.
Patent Information
- Application Number
- CN202411469669.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, the catalyst for directly preparing ethylenediamine in ethylene glycol has low conversion rate of ethylenediamine and low yield of ethylenediamine and piperazine, and the produced by-products are many and difficult to separate. The catalyst preparation method is complicated and cannot be Meet the needs of industrial applications.
The CuNiAg/Al2O3 catalyst was prepared for one-step reaction of ethylene glycol and ammonia gas by doping metal silver on the alumina support by co-precipitation method, impregnation method, Galvanic replacement method and deposition precipitation method. , achieve high activity and high selectivity preparation of ethylenediamine and piperazine.
It significantly improves the yield of ethylenediamine and piperazine, reduces the generation of by-products, simplifies the catalyst preparation process and reaction operations, reduces costs, and is suitable for industrial applications.
Smart Images

Figure BDA0005094347900000171 
Figure BDA0005094347900000181 
Figure BDA0005094347900000182
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalytic technology, and in particular to a method for preparing a copper-nickel-silver composite metal catalyst and application of the catalyst in preparing ethylenediamine and co-producing piperazine by catalytic amination of ethylene glycol. Background Art
[0002] Ethylene glycol (EG) is an important organic chemical raw material. In recent years, due to the rapid expansion of the coal-to-EG industry, the global EG market is facing severe problems of sluggish market and overcapacity. Therefore, making good layout of EG downstream high-end fine chemicals and improving product added value are not only of practical significance for alleviating EG overcapacity and realizing its high-value utilization, but also of great significance for solving resource and energy problems, efficiently utilizing biomass resources, and realizing carbon cycle. Ethylene diamine (EDA) is an important basic chemical raw material, used as solvent, stabilizer, chelating agent, synthetic resin, pesticide bactericide, reactive dye intermediate, drug, inhibitor. At present, the main methods for industrial production of ethylenediamine are ethylene dichloride method (EDC) and ethanolamine method (MEA), accounting for about 60% and 40% of global production respectively. The former uses a large amount of acid and alkali in the production process, and has the disadvantages of severe equipment corrosion and poor product quality; the latter ethanolamine is made by the reaction of ethylene oxide and ammonia, and ethylene oxide is made by ethylene and oxygen. Its main raw materials come from petroleum and are restricted by the development of the petrochemical industry. In recent years, the application of ethylenediamine in my country has developed rapidly, and the domestic demand is strong. However, the domestic ethylenediamine production enterprises are small in scale, high in cost, serious in pollution and poor in product quality. The total production capacity is seriously insufficient. More than 90% of the demand for ethylenediamine depends on imports. It has become a fine chemical intermediate that needs to be developed in my country. [1] Therefore, developing a highly active and highly selective ethylene glycol amination system has very important economic value and application significance.
[0003] Due to the vigorous development of coal chemical industry in my country in recent years, the cost advantage brought by coal-to-ethylene glycol technology is significantly higher than that of petroleum-to-ethylene glycol technology, which also makes the direct preparation of ethylenediamine from ethylene glycol a new focus.
[0004] Patent application CN101384542A filed by BASF Europe discloses a method for producing ethyleneamine and ethanolamine from ethylene glycol, using a two-stage reaction process. The first stage can use a known catalyst, and the second stage uses a catalyst mainly composed of Ru and Co. The pressure is 200 bar, the temperature is 150-170°C, and the conversion rate of ethylene glycol is 46%.
[0005] CN102233272A discloses a catalyst for directly preparing ethylenediamine from ethylene glycol, using Cu and Ni as main components and Zr as auxiliary component. The catalyst is prepared by coprecipitation method through precipitation, aging, washing, drying, roasting and other steps, and then the activity of the catalyst is improved through a reduction process.
[0006] CN102658162A discloses a catalyst for synthesizing ethyleneamine and a method for preparing ethyleneamine. The catalyst involved in the patent application uses Co and Ni as active components and an ammoniation-treated carrier to synthesize ethyleneamine products under hydrogenation conditions.
[0007] Based on the existing technology, the catalyst for directly preparing ethylenediamine from ethylene glycol has the following problems: low ethylene glycol conversion rate, low yield of high value-added chemicals ethylenediamine and piperazine, a large number of by-products generated, which cannot be separated and purified, and complex catalyst preparation methods. Summary of the invention
[0008] The invention aims to overcome the disadvantages of the prior art, discloses a method for preparing a copper-nickel-silver composite metal catalyst and its application in preparing ethylenediamine and co-producing piperazine by catalytic amination of ethylene glycol. The invention relates to a novel composite metal catalyst for preparing ethylenediamine and co-producing piperazine by catalytic amination of ethylene glycol and a preparation method thereof. The catalyst is doped with metallic silver in copper-nickel by a coprecipitation method, an impregnation method, a Galvanic replacement method and a sedimentation precipitation method. The prepared copper-nickel-silver composite metal catalyst can greatly improve the yield of high value-added chemicals ethylenediamine and piperazine in preparing ethylenediamine and co-producing piperazine by catalytic amination of ethylene glycol; in addition to ethylenediamine and piperazine, the catalytic product does not contain ethanolamine and diethylenetriamine by-products; the catalyst preparation process is simple, the raw materials are low-cost, the catalyst does not require special equipment in the catalytic reaction, the catalytic reaction is simple to operate, and the high-activity and high-selectivity ethylenediamine amination of ethylene glycol is achieved to prepare ethylenediamine and piperazine; the catalyst is conducive to industrial use and has a strong prospect for promotion and application.
[0009] In a first aspect, the present invention provides a catalyst comprising a carrier and an active component, wherein the carrier is alumina, and the active component metals are Cu, Ni and Ag.
[0010] In a second aspect, the present invention provides a method for preparing the catalyst, which includes a coprecipitation method, an impregnation method, a Galvanic displacement method, and a deposition precipitation method. Specifically, the precursor of the active component is loaded on a carrier, dried, calcined, and reduced.
[0011] In a third aspect, the present invention provides an application of the catalyst prepared by the present invention in the amination of ethylene glycol to prepare ethylenediamine, the application comprising: contacting ethylene glycol, hydrogen and ammonia with the catalyst of the present invention to react to prepare ethylenediamine.
[0012] The catalyst of the present invention can catalyze the one-step reaction of ethylene glycol and ammonia to prepare ethylenediamine and piperazine with high activity and high selectivity, and at the same time helps to improve the activity and stability of the catalyst. The catalyst preparation process of the present invention is simple, low-cost, and does not need to undergo special treatments such as ammoniation treatment. In a preferred embodiment of the present invention, since dehydrogenation and hydrogenation are key steps of the reaction, and copper-based catalysts, as good alcohol dehydrogenation catalysts, will sinter and deactivate at high temperatures; nickel-based catalysts are good hydrogenation catalysts. Therefore, using Cu and Ni as the main active components and Ag metal as the auxiliary active component can better complete the two key steps of dehydrogenation and hydrogenation, and better achieve the one-step reaction of ethylene glycol and ammonia to prepare ethylenediamine and piperazine.
[0013] In order to achieve the above technical effects, the following technical solutions are adopted:
[0014] A method for preparing a copper-nickel-silver composite metal catalyst, comprising a coprecipitation method, an impregnation method, a Galvanic replacement method, and a deposition precipitation method;
[0015] The specific steps of the coprecipitation method are:
[0016] Copper nitrate solution, nickel nitrate solution, silver nitrate solution and aluminum nitrate solution are prepared respectively, and according to the composition of the target catalyst, the copper nitrate solution, nickel nitrate solution, silver nitrate solution and aluminum nitrate solution are uniformly mixed, and sodium carbonate solution is added dropwise in an ice water bath to generate a precipitate, and the pH value of the reaction end point is controlled; aging; washing the precipitate with deionized water to neutrality; drying; roasting; grinding into powder, and reducing to obtain the copper-nickel-silver composite metal catalyst;
[0017] The specific steps of the impregnation method are:
[0018] Copper nitrate solution, nickel nitrate solution and silver nitrate solution are prepared respectively, and according to the composition of the target catalyst, the copper nitrate solution, nickel nitrate solution and silver nitrate solution are mixed evenly, and then γ-Al2O3 is added and mixed evenly; aging is performed to remove water from the reaction solution to obtain a solid; drying; roasting; grinding into powder, and reducing to obtain the copper-nickel-silver composite metal catalyst;
[0019] The specific steps of the Galvanic replacement method are:
[0020] Copper nitrate solution, nickel nitrate solution and aluminum nitrate solution are prepared respectively, and according to the composition of the target catalyst, the copper nitrate solution, nickel nitrate solution and aluminum nitrate solution are uniformly mixed, and sodium carbonate solution is added dropwise in an ice water bath to generate a precipitate; the pH value at the reaction end point is controlled; aging is performed; the precipitate is washed with deionized water until it is neutral; after drying; roasting; grinding into powder, and reducing to obtain a catalyst precursor; all the obtained precursors are added to ethanol to prepare a silver nitrate solution, and the silver nitrate solution is added dropwise to the precursor, and aging is performed; washing is performed to obtain a precipitate; and drying is performed to obtain the copper-nickel-silver composite metal catalyst;
[0021] The specific steps of the sedimentation precipitation method are:
[0022] Copper nitrate solution, nickel nitrate solution and silver nitrate solution are prepared respectively, and according to the composition of the target catalyst, the copper nitrate solution, nickel nitrate solution and silver nitrate solution are evenly mixed, and then γ-Al2O3 is added and mixed evenly; sodium carbonate solution is added dropwise under ice bath conditions to generate precipitation, and the pH value of the reaction end point is controlled; aging; washing the precipitation with deionized water to neutrality; drying; roasting; grinding into powder, and reducing to obtain the copper-nickel-silver composite metal catalyst.
[0023] Furthermore, in the coprecipitation method, the molar concentrations of the copper nitrate solution and the nickel nitrate solution are 0.2-0.25 mol / L, respectively; the molar concentration of the silver nitrate solution is 15-25 mmol / L; the molar concentration of the aluminum nitrate solution is 0.5-0.7 mol / L; the molar concentrations of the sodium carbonate solution are 0.8-2.0 mol / L, respectively; and the volume ratio of the copper nitrate solution, the nickel nitrate solution, the silver nitrate solution, the aluminum nitrate solution and the sodium carbonate solution is 15-20:15-20:10-15:15-20:25-30.
[0024] Furthermore, in the co-precipitation method, the reaction endpoint pH is controlled to be 9-11; the aging is carried out for 3-5 hours; the precipitate is dried at 100-110°C for 10-12 hours, and calcined at 400-500°C for 3-4 hours; and reduced at 350-500°C for 2-3 hours at a hydrogen flow rate of 5 mL / min.
[0025] Furthermore, in the impregnation method, the molar concentrations of the copper nitrate solution and the nickel nitrate solution are 0.2-0.25 mol / L respectively; the molar concentration of the silver nitrate solution is 15-25 mmol / L; the masses of copper nitrate, nickel nitrate, silver nitrate and γ-Al2O3 in the copper nitrate solution, nickel nitrate solution and silver nitrate solution are 7.2480-12.10:8.7237-14.50:0.2548-0.6370:15-20.
[0026] Furthermore, in the impregnation method, the solid is aged at room temperature for 3-5 hours and the water is removed by rotary evaporation; the solid is dried at 100-110°C for 10-12 hours, calcined at 400-500°C for 3-4 hours, and reduced at 350-500°C for 2-3 hours at a hydrogen flow rate of 5 mL / min.
[0027] Furthermore, in the Galvanic replacement method, the molar concentrations of the copper nitrate solution and the nickel nitrate solution are 0.2-0.25 mol / L, respectively; the molar concentration of the silver nitrate solution is 15-25 mmol / L; the molar concentration of the aluminum nitrate solution is 0.5-0.7 mol / L; the molar concentrations of the sodium carbonate solution are 0.8-2.0 mol / L, respectively; and the volume ratio of the copper nitrate solution, the nickel nitrate solution, the aluminum nitrate solution and the sodium carbonate solution is 15-20:15-20:15-20:25-30.
[0028] Furthermore, in the Galvanic replacement method, the reaction endpoint pH is controlled to be 9-11; the reaction is aged for 3-5 hours; the precipitate is dried at 100-110°C for 10-12 hours, and calcined at 400-500°C for 3-4 hours; the precipitate is reduced at 350-500°C for 2-3 hours at a hydrogen flow rate of 5 mL / min; a silver nitrate solution is added to the catalyst precursor, and the catalyst is aged at 35°C for 3-5 hours; the precipitate is washed by centrifugation with ethanol three times to obtain a precipitate; and the precipitate is vacuum dried at 40°C for 8 hours.
[0029] Furthermore, in the deposition precipitation method, the molar concentrations of the copper nitrate solution and the nickel nitrate solution are 0.2-0.25 mol / L, respectively; the molar concentration of the silver nitrate solution is 15-25 mmol / L; the molar concentration of the sodium carbonate solution is 0.8-2.0 mol / L, respectively; the masses of copper nitrate, nickel nitrate, silver nitrate and sodium carbonate to γ-Al2O3 in the copper nitrate solution, nickel nitrate solution, silver nitrate solution and sodium carbonate solution are 7.2480-12.10:8.7237-14.50:0.2548-0.6370:21.20-63.60:15-20; the reaction endpoint pH is controlled to be 9-11; aging is performed for 3-5 hours; the precipitate is dried at 100-110°C for 10-12 hours, and calcined at 400-500°C for 3-4 hours; and reduced at 350-500°C for 2-3 hours at a hydrogen flow rate of 5 mL / min.
[0030] A copper-nickel-silver composite metal catalyst is prepared by any one of the above-mentioned preparation methods.
[0031] The copper-nickel-silver composite metal catalyst prepared by any of the preparation methods described above is used for catalytic amination of ethylene glycol to prepare ethylenediamine and co-produce piperazine.
[0032] The beneficial effects of the present invention are:
[0033] The invention discloses a method for preparing a copper-nickel-silver composite metal catalyst and application thereof in preparing ethylenediamine and co-producing piperazine by catalytic amination of ethylene glycol. The invention relates to a novel composite metal catalyst for synthesizing ethylenediamine and co-producing piperazine by catalytic amination of ethylene glycol and a preparation method thereof. The catalyst is doped with metallic silver in copper-nickel by a coprecipitation method, an impregnation method, a Galvanic replacement method and a sedimentation precipitation method. The prepared copper-nickel-silver composite metal catalyst can greatly improve the yield of high value-added chemicals ethylenediamine and piperazine in preparing ethylenediamine and co-producing piperazine by catalytic amination of ethylene glycol. In addition to ethylenediamine and piperazine, the catalytic product does not contain ethanolamine and diethylenetriamine by-products. The catalyst preparation process is simple, the raw materials are low-cost, the catalyst does not require special equipment in the catalytic reaction, the catalytic reaction operation is simple, it is conducive to industrial use, and has a strong prospect for promotion and application.
[0034] 1. This method uses the synergistic catalytic effect between metallic silver and copper-nickel catalysts to not only improve the catalytic activity of the catalyst, but also ultimately achieve a high-efficiency and high-selectivity process for preparing ethylenediamine and piperazine by amination of ethylene glycol;
[0035] 2. The CuNiAg / Al2O3 catalyst of the present invention can catalyze the amination of ethylene glycol to produce ethylenediamine and piperazine with high efficiency and high selectivity, and has important industrial application value. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0038] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.
[0039] The following catalyst activity testing and evaluation methods were used in both the examples and comparative examples.
[0040] A method for preparing ethylenediamine by catalyzing the amination of ethylene glycol using a catalyst: 200 mg of a metal catalyst and 1 mmol of ethylene glycol are added to a high-pressure reactor, and 3 MPa of hydrogen and 7 g of ammonia are introduced. The reaction temperature is 180° C. and the reaction time is 13 h. After the reaction is completed, the reactor is cooled to -18° C. and the liquid and the catalyst are separated by centrifugation.
[0041] The autoclave reactor was used as an instrument for evaluating the activity of the catalyst. After the reaction, the components were analyzed by gas chromatography to calculate the conversion of ethylene glycol and the yields of ethylenediamine, piperazine, ethanolamine and diethylenetriamine.
[0042] Example 1
[0043] Preparation of CuNiAgAlO by coprecipitation method x Catalyst. Prepare 15mL of 0.2mol / L copper nitrate (724.80mg) and nickel nitrate solution (872.37mg), 10mL of 15mmol / L silver nitrate solution (25.48mg) and 15mL of 0.5mol / L aluminum nitrate solution (2.81g) in a round-bottom flask, and add 25mL of 0.8mol / L sodium carbonate solution (2.12g) dropwise in an ice-water bath to generate a precipitate. The pH of the endpoint is controlled to be 9. Aging for 3h, washing the precipitate with deionized water to neutrality, drying the precipitate at 100℃ for 10h, and calcining at 400℃ for 3h. Grind into powder, reduce at 350℃ for 2h at a hydrogen flow rate of 5mL / min, and finally obtain CuNiAgAlO x Catalyst. The evaluation results are shown in Table 1.
[0044] Example 2
[0045] Preparation of CuNiAgAlO by coprecipitation method x Catalyst. Prepare 20mL of 0.25mol / L copper nitrate (1.21g) and nickel nitrate solution (1.45g), 15mL of 25mmol / L silver nitrate solution (63.70mg) and 20mL of 0.7mol / L aluminum nitrate solution (5.25g) in a round-bottom flask, and add 30mL of 2.0mol / L sodium carbonate solution (6.36g) dropwise in an ice-water bath to generate a precipitate. The pH at the end point is controlled to be 11. Aging for 5h, washing the precipitate with deionized water until neutral, drying the precipitate at 110℃ for 12h, and calcining at 500℃ for 4h. Grind into powder, reduce at 500℃ for 3h at a hydrogen flow rate of 5mL / min, and finally obtain CuNiAgAlO x Catalyst. The evaluation results are shown in Table 1.
[0046] Comparative Example 1
[0047] Preparation of NiAgAlO by coprecipitation method x Catalyst. The method of Example 1 was followed, except that copper nitrate was not added. The evaluation results are shown in Table 1.
[0048] Comparative Example 2
[0049] Preparation of CuAgAlO by coprecipitation method x Catalyst. The method of Example 1 was followed, except that nickel nitrate was not added. The evaluation results are shown in Table 1.
[0050] Comparative Example 3
[0051] Preparation of CuNiAlO by coprecipitation method x Catalyst. The method of Example 1 was followed, except that no silver nitrate was added. The evaluation results are shown in Table 1.
[0052] Comparative Example 4
[0053] Preparation of AgAlO by coprecipitation method x Catalyst. The method of Example 1 was followed, except that copper nitrate and nickel nitrate were not added. The evaluation results are shown in Table 1.
[0054] Comparative Example 5
[0055] Preparation of NiAlO by coprecipitation method x Catalyst. The method of Example 1 was followed, except that copper nitrate and silver nitrate were not added. The evaluation results are shown in Table 1.
[0056] Comparative Example 6
[0057] Preparation of CuAlO by coprecipitation method x Catalyst. The method of Example 1 was followed, except that nickel nitrate and silver nitrate were not added. The evaluation results are shown in Table 1.
[0058] Comparative Example 7
[0059] Preparation of CuNiAuAlO by coprecipitation method x Catalyst. The method of Example 1 was followed, except that silver nitrate was replaced with an equal molar amount of chloroauric acid. The evaluation results are shown in Table 1.
[0060] Comparative Example 8
[0061] Preparation of CuNiPdAlO by coprecipitation method x Catalyst: The method of Example 1 was followed, except that silver nitrate was replaced with an equal molar amount of chloropalladic acid. The evaluation results are shown in Table 1.
[0062] Comparative Example 9
[0063] Preparation of CuNiRuAlO by coprecipitation method xCatalyst. The method of Example 1 was followed, except that silver nitrate was replaced with an equal molar amount of ruthenium chloride. The evaluation results are shown in Table 1.
[0064] Comparative Example 10
[0065] Preparation of CuNiCoAlO by coprecipitation method x Catalyst. The method of Example 1 was followed, except that the silver nitrate was replaced with an equimolar amount of cobalt nitrate. The evaluation results are shown in Table 1.
[0066] Comparative Example 11
[0067] The CuNiAgCeO2 catalyst was prepared by coprecipitation method. The method of Example 1 was followed, except that aluminum nitrate was replaced by an equal molar amount of cerium nitrate. The evaluation results are shown in Table 1.
[0068] Comparative Example 12
[0069] The CuNiAgZrO2 catalyst was prepared by coprecipitation method. The method of Example 1 was followed, except that aluminum nitrate was replaced by an equal molar amount of zirconium nitrate. The evaluation results are shown in Table 1.
[0070] Example 3
[0071] The CuNiAg / γ-Al2O3 catalyst was prepared by impregnation method. 15mL of 0.2mol / L copper nitrate (724.80mg) and nickel nitrate solution (872.37mg), 10mL of 15mmol / L silver nitrate solution (25.48mg) were prepared in a round-bottom flask, and 1.5g of γ-Al2O3 was added and mixed evenly. Aged at room temperature for 3h, and the water was removed by rotary evaporation to obtain a solid. Dry at 100℃ for 10h and calcine at 400℃ for 3h. Grind into powder, reduce at 350℃ for 2h under a hydrogen flow rate of 5mL / min, and finally obtain the CuNiAg / γ-Al2O3 catalyst. The evaluation results are shown in Table 2.
[0072] Example 4
[0073] The CuNiAg / γ-Al2O3 catalyst was prepared by impregnation method. 20mL of 0.25mol / L copper nitrate (1.21g) and nickel nitrate solution (1.45g), 15mL of 25mmol / L silver nitrate solution (63.70mg) were prepared in a round-bottom flask, and 2.0g of γ-Al2O3 was added and mixed evenly. Aged at room temperature for 5h, and the water was removed by rotary evaporation to obtain a solid. Dry at 110℃ for 12h and calcine at 500℃ for 4h. Grind into powder, reduce at 500℃ for 3h at a hydrogen flow rate of 5mL / min, and finally obtain the CuNiAg / γ-Al2O3 catalyst. The evaluation results are shown in Table 2.
[0074] Comparative Example 13
[0075] The NiAg / γ-Al2O3 catalyst was prepared by impregnation method according to the method of Example 3, except that copper nitrate was not added. The evaluation results are shown in Table 2.
[0076] Comparative Example 14
[0077] The CuAg / γ-Al2O3 catalyst was prepared by impregnation method according to the method of Example 3, except that nickel nitrate was not added. The evaluation results are shown in Table 2.
[0078] Comparative Example 15
[0079] The CuNi / γ-Al2O3 catalyst was prepared by impregnation method according to the method of Example 3, except that no silver nitrate was added. The evaluation results are shown in Table 2.
[0080] Comparative Example 16
[0081] The Ag / γ-Al2O3 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that copper nitrate and nickel nitrate were not added. The evaluation results are shown in Table 2.
[0082] Comparative Example 17
[0083] The Ni / γ-Al2O3 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that copper nitrate and silver nitrate were not added. The evaluation results are shown in Table 2.
[0084] Comparative Example 18
[0085] The Cu / γ-Al2O3 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that nickel nitrate and silver nitrate were not added. The evaluation results are shown in Table 2.
[0086] Comparative Example 19
[0087] The CuNiAu / γ-Al2O3 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that silver nitrate was replaced by an equal molar amount of chloroauric acid. The evaluation results are shown in Table 2.
[0088] Comparative Example 20
[0089] The CuNiPd / γ-Al2O3 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that silver nitrate was replaced by an equal molar amount of chloropalladic acid. The evaluation results are shown in Table 2.
[0090] Comparative Example 21
[0091] The CuNiRu / γ-Al2O3 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that the silver nitrate was replaced by an equal molar amount of ruthenium chloride. The evaluation results are shown in Table 2.
[0092] Comparative Example 22
[0093] The CuNiCo / γ-Al2O3 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that the silver nitrate was replaced by an equimolar amount of cobalt nitrate. The evaluation results are shown in Table 2.
[0094] Comparative Example 23
[0095] The CuNiAg / SiO2 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that γ-Al2O3 was replaced by an equal molar amount of SiO2. The evaluation results are shown in Table 2.
[0096] Comparative Example 24
[0097] The CuNiAg / TiO2 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that γ-Al2O3 was replaced by an equal molar amount of TiO2. The evaluation results are shown in Table 2.
[0098] Comparative Example 25
[0099] The CuNiAg / CeO2 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that γ-Al2O3 was replaced by an equal molar amount of CeO2. The evaluation results are shown in Table 2.
[0100] Comparative Example 26
[0101] The CuNiAg / ZrO2 catalyst was prepared by impregnation method. The method of Example 3 was followed, except that γ-Al2O3 was replaced by an equal molar amount of ZrO2. The evaluation results are shown in Table 2.
[0102] Example 5
[0103] Preparation of Ag-CuNiAlO by Galvanic Replacement Method xCatalyst. The preparation method is as follows: prepare 15mL of 0.2mol / L copper nitrate (724.80mg) and nickel nitrate solution (872.37mg), 15mL of 0.5mol / L aluminum nitrate (2.81g) solution in a round-bottom flask, add 25mL of 0.8mol / L sodium carbonate solution (2.12g) in an ice-water bath, generate a precipitate, and control the pH of the end point to be 9. Aging for 3h, washing the precipitate with deionized water to neutrality, drying the precipitate at 100℃ for 10h, and calcining at 400℃ for 3h. Grind into powder, reduce at 350℃ for 2h at a hydrogen flow rate of 5mL / min to obtain a catalyst precursor. Add all the obtained precursors to a round-bottom flask containing 25mL of ethanol, add 10mL of 15mmol / L silver nitrate solution (25.48mg), and age at 35℃ for 3h. Wash with ethanol by centrifugation for 3 times to obtain a precipitate. Dry under vacuum at 40 °C for 8 h to obtain Ag-CuNiAlO x Catalyst. The evaluation results are shown in Table 3.
[0104] Example 6
[0105] Preparation of Ag-CuNiAlO by Galvanic Replacement Method x Catalyst. The preparation method is as follows: prepare 20 mL of 0.25 mol / L copper nitrate (1.21 g) and nickel nitrate solution (1.45 g), 20 mL of 0.7 mol / L aluminum nitrate solution (5.25 g) in a round-bottom flask, and add 30 mL of 2.0 mol / L sodium carbonate solution (6.36 g) in an ice-water bath to generate a precipitate. The pH of the end point is controlled to be 11. Aging for 5 hours, washing the precipitate with deionized water until neutral, drying the precipitate at 110 ° C for 12 hours, and calcining at 500 ° C for 4 hours. Grind into powder, reduce at 500 ° C for 3 hours at a hydrogen flow rate of 5 mL / min to obtain a catalyst precursor. All the obtained precursors are added to a round-bottom flask containing 25 mL of ethanol, and 15 mL of 25 mmol / L silver nitrate solution (63.70 mg) is added dropwise, and aged at 35 ° C for 5 hours. Wash with ethanol by centrifugation for 3 times to obtain a precipitate. Dry under vacuum at 40 °C for 8 h to obtain Ag-CuNiAlO x Catalyst. The evaluation results are shown in Table 3.
[0106] Comparative Example 27
[0107] Preparation of Ag-NiAlO by Galvanic Replacement Method x Catalyst. The method of Example 5 was followed, except that copper nitrate was not added. The evaluation results are shown in Table 3.
[0108] Comparative Example 28
[0109] Preparation of Ag-CuAlO by Galvanic Replacement Method x Catalyst. The method of Example 5 was followed, except that nickel nitrate was not added. The evaluation results are shown in Table 3.
[0110] Comparative Example 29
[0111] Preparation of CuNiAlO by Galvanic Replacement Method x Catalyst. The method of Example 5 was followed, except that no silver nitrate was added. The evaluation results are shown in Table 3.
[0112] Comparative Example 30
[0113] Preparation of AgAlO by Galvanic Replacement Method x Catalyst. The method of Example 5 was followed, except that copper nitrate and nickel nitrate were not added. The evaluation results are shown in Table 3.
[0114] Comparative Example 31
[0115] Preparation of NiAlO by Galvanic Replacement Method x Catalyst. The method of Example 5 was followed, except that copper nitrate and silver nitrate were not added. The evaluation results are shown in Table 3.
[0116] Comparative Example 32
[0117] Preparation of CuAlO by Galvanic Replacement x Catalyst. The method of Example 5 was followed, except that nickel nitrate and silver nitrate were not added. The evaluation results are shown in Table 3.
[0118] Comparative Example 33
[0119] Preparation of Au-CuNiAlO by Galvanic Replacement x Catalyst. The method of Example 5 was followed, except that silver nitrate was replaced with an equal molar amount of chloroauric acid. The evaluation results are shown in Table 3.
[0120] Comparative Example 34
[0121] Preparation of Pd-CuNiAlO by Galvanic Replacement Method x Catalyst. The method of Example 5 was followed, except that silver nitrate was replaced with an equal molar amount of chloropalladic acid. The evaluation results are shown in Table 3.
[0122] Comparative Example 35
[0123] Preparation of Ru-CuNiAlO by Galvanic Replacement Method x Catalyst. The method of Example 5 was followed, except that the silver nitrate was replaced with an equal molar amount of ruthenium chloride. The evaluation results are shown in Table 3.
[0124] Comparative Example 36
[0125] Preparation of Co-CuNiAlO by Galvanic Replacement Method x Catalyst. The method of Example 5 was followed, except that the silver nitrate was replaced with an equimolar amount of cobalt nitrate. The evaluation results are shown in Table 3.
[0126] Comparative Example 37
[0127] Ag-CuNiCeO2 catalyst was prepared by Galvanic replacement method. The method of Example 5 was followed, except that aluminum nitrate was replaced by an equal molar amount of cerium nitrate. The evaluation results are shown in Table 3.
[0128] Comparative Example 38
[0129] Ag-CuNiZrO2 catalyst was prepared by Galvanic replacement method. The method of Example 5 was followed, except that aluminum nitrate was replaced by an equal molar amount of zirconium nitrate. The evaluation results are shown in Table 3.
[0130] Example 7
[0131] The CuNiAg / γ-Al2O3 catalyst was prepared by the deposition precipitation method. The preparation method is as follows: prepare 15mL of 0.2mol / L copper nitrate (724.80mg) and nickel nitrate solution (872.37mg), 10mL of 15mmol / L silver nitrate solution (25.48mg) in a round-bottom flask, and then add 1.5gγ-Al2O3 and mix evenly. In an ice-water bath, add 25mL of 0.8mol / L sodium carbonate solution (2.12g) dropwise to form a precipitate, and control the pH of the end point to 9. Aging for 3h, washing the precipitate with deionized water to neutrality, drying the precipitate at 100℃ for 10h, and calcining at 400℃ for 3h. Grind into powder, reduce at 350℃ for 2h under a hydrogen flow rate of 5mL / min, and finally obtain the CuNiAg / γ-Al2O3 catalyst. The evaluation results are shown in Table 4.
[0132] Example 8
[0133] The CuNiAg / γ-Al2O3 catalyst was prepared by the deposition precipitation method. The preparation method is as follows: prepare 20mL of 0.25mol / L copper nitrate (1.21g) and nickel nitrate solution (1.45g), 15mL of 25mmol / L silver nitrate solution (63.70mg) in a round-bottom flask, and then add 2.0gγ-Al2O3 and mix evenly. In an ice-water bath, add 30mL of 2.0mol / L sodium carbonate solution (6.36g) dropwise to form a precipitate, and control the pH of the end point to be 11. Aging for 5h, washing the precipitate with deionized water to neutrality, drying the precipitate at 110℃ for 12h, and calcining at 500℃ for 4h. Grind into powder, reduce at 500℃ for 3h at a hydrogen flow rate of 5mL / min, and finally obtain the CuNiAg / γ-Al2O3 catalyst. The evaluation results are shown in Table 4.
[0134] Comparative Example 39
[0135] The NiAg / γ-Al2O3 catalyst was prepared by a deposition precipitation method according to the method of Example 7, except that copper nitrate was not added. The evaluation results are shown in Table 4.
[0136] Comparative Example 40
[0137] The CuAg / γ-Al2O3 catalyst was prepared by the deposition precipitation method according to the method of Example 7, except that nickel nitrate was not added. The evaluation results are shown in Table 4.
[0138] Comparative Example 41
[0139] The CuNi / γ-Al2O3 catalyst was prepared by the deposition precipitation method according to the method of Example 7, except that no silver nitrate was added. The evaluation results are shown in Table 4.
[0140] Comparative Example 42
[0141] Ag / γ-Al2O3 catalyst was prepared by the deposition precipitation method. The method of Example 7 was followed, except that copper nitrate and nickel nitrate were not added. The evaluation results are shown in Table 4.
[0142] Comparative Example 43
[0143] The Ni / γ-Al2O3 catalyst was prepared by a deposition precipitation method. The method of Example 7 was followed, except that copper nitrate and silver nitrate were not added. The evaluation results are shown in Table 4.
[0144] Comparative Example 44
[0145] The Cu / γ-Al2O3 catalyst was prepared by the deposition precipitation method. The method of Example 7 was followed, except that nickel nitrate and silver nitrate were not added. The evaluation results are shown in Table 4.
[0146] Comparative Example 45
[0147] The CuNiAu / γ-Al2O3 catalyst was prepared by the deposition precipitation method. The method of Example 7 was followed, except that the silver nitrate was replaced by an equal molar amount of chloroauric acid. The evaluation results are shown in Table 4.
[0148] Comparative Example 46
[0149] The CuNiPd / γ-Al2O3 catalyst was prepared by the deposition precipitation method. The method of Example 7 was followed, except that the silver nitrate was replaced by an equal molar amount of chloropalladic acid. The evaluation results are shown in Table 4.
[0150] Comparative Example 47
[0151] The CuNiRu / γ-Al2O3 catalyst was prepared by the deposition precipitation method. The method of Example 7 was followed, except that the silver nitrate was replaced by an equal molar amount of ruthenium chloride. The evaluation results are shown in Table 4.
[0152] Comparative Example 48
[0153] The CuNiCo / γ-Al2O3 catalyst was prepared by the deposition precipitation method. The method of Example 7 was followed, except that the silver nitrate was replaced by an equimolar amount of cobalt nitrate. The evaluation results are shown in Table 4.
[0154] Comparative Example 49
[0155] The CuNiAg / SiO2 catalyst was prepared by the deposition precipitation method. The method of Example 7 was followed, except that γ-Al2O3 was replaced by an equal molar amount of SiO2. The evaluation results are shown in Table 4.
[0156] Comparative Example 50
[0157] The CuNiAg / TiO2 catalyst was prepared by the deposition precipitation method. The method of Example 7 was followed, except that γ-Al2O3 was replaced by an equal molar amount of TiO2. The evaluation results are shown in Table 4.
[0158] Comparative Example 51
[0159] The CuNiAg / CeO2 catalyst was prepared by the deposition precipitation method. The method of Example 7 was followed, except that γ-Al2O3 was replaced by an equal molar amount of CeO2. The evaluation results are shown in Table 4.
[0160] Comparative Example 52
[0161] The CuNiAg / ZrO2 catalyst was prepared by the deposition precipitation method. The method of Example 7 was followed, except that γ-Al2O3 was replaced by an equal molar amount of ZrO2. The evaluation results are shown in Table 4.
[0162] The catalysts in Examples 1-8 and Comparative Examples 1-52 were used to carry out experiments on the preparation of ethylenediamine by amination of ethylene glycol.
[0163] Ethylene glycol is 1 mmol (62 mg), catalyst is 200 mg, mesitylene is 15 mL, ammonia is 7 g, hydrogen pressure is 3 MPa, reaction temperature is 180°C, the reaction is carried out in a high pressure reactor for 13 hours, the reaction liquid is washed out with ethanol, the catalyst and the reaction liquid are separated by centrifugation, the liquid product is analyzed by gas chromatography, the conversion rate of ethylene glycol and the yields of ethylenediamine, piperazine, ethanolamine and diethylenetriamine are calculated, and the reaction results are shown in Tables 1-4.
[0164] Table 1 Performance evaluation of catalysts prepared by coprecipitation method for the amination of ethylene glycol to ethylenediamine
[0165]
[0166]
[0167] It can be seen from Table 1 that CuNiAgAlO x The catalyst has the best performance in catalyzing the amination of ethylene glycol to prepare ethylenediamine. x If any of the components in the catalyst is missing or replaced, the yields of ethylenediamine and piperazine will decrease, and the yields of by-products ethanolamine and diethylenetriamine will increase.
[0168] Table 2 Performance evaluation of catalysts prepared by impregnation method for the amination of ethylene glycol to ethylenediamine
[0169]
[0170]
[0171] As can be seen from Table 2, the performance of CuNiAg / γ-Al2O3 catalyst in catalyzing the amination of ethylene glycol to prepare ethylenediamine is the best. Example 3 Compared with Comparative Examples 13-26, the CuNiAg / γ-Al2O3 catalyst lacks any of the components. x If any of the components in the catalyst is missing or replaced, the yields of ethylenediamine and piperazine will decrease, and the yields of by-products ethanolamine and diethylenetriamine will increase.
[0172] Table 3 Performance evaluation of catalysts prepared by Galvanic displacement method for the amination of ethylene glycol to ethylenediamine
[0173]
[0174]
[0175] As can be seen from Table 3, the Ag-CuNi / γ-Al2O3 catalyst has the best performance in catalyzing the amination of ethylene glycol to prepare ethylenediamine. x If any of the components in the catalyst is missing or replaced, the yields of ethylenediamine and piperazine will decrease, and the yields of by-products ethanolamine and diethylenetriamine will increase.
[0176] Table 4 Performance evaluation of catalysts prepared by sedimentation precipitation method for the amination of ethylene glycol to ethylenediamine
[0177]
[0178]
[0179] As can be seen from Table 4, the performance of CuNiAg / γ-Al2O3 catalyst in catalyzing the amination of ethylene glycol to prepare ethylenediamine is the best. Compared with Comparative Examples 39-44, when any of the components in the CuNiAg / γ-Al2O3 catalyst are missing, the yields of ethylenediamine and piperazine will decrease, and the yields of the byproducts ethanolamine and diethylenetriamine will increase. Compared with Comparative Examples 45-48, in Example 7, Ag metal can better assist the CuNi main active component than other metals, and better realize the one-step reaction of ethylene glycol and ammonia to prepare ethylenediamine. Compared with Comparative Examples 49-52, in Example 7, γ-Al2O3 is the best catalyst carrier for this reaction.
[0180] In summary, the present invention discloses a method for preparing a copper-nickel-silver composite metal catalyst and its application in preparing ethylenediamine and co-producing piperazine by catalytic amination of ethylene glycol. The present invention relates to a novel composite metal catalyst for synthesizing ethylenediamine and co-producing piperazine by catalytic amination of ethylene glycol and a preparation method thereof. The catalyst is doped with metallic silver in copper-nickel by a coprecipitation method, an impregnation method, a Galvanic replacement method and a sedimentation precipitation method. The prepared copper-nickel-silver composite metal catalyst can greatly improve the yield of high value-added chemicals ethylenediamine and piperazine in preparing ethylenediamine and co-producing piperazine by catalytic amination of ethylene glycol; in addition to ethylenediamine and piperazine, the catalytic product does not contain ethanolamine and diethylenetriamine by-products. The catalyst preparation process is simple, the raw materials are low-cost, the catalyst does not require special equipment in the catalytic reaction, the catalytic reaction operation is simple, it is conducive to industrial use, and has a strong prospect for promotion and application.
[0181] At this point, those skilled in the art recognize that, although the embodiments of the present invention have been shown and described in detail herein, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the contents disclosed in the present invention without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.
Claims
1. A method for preparing a copper-nickel-silver composite metal catalyst, characterized in that: The preparation method includes co-precipitation method, impregnation method, Galvanic replacement method, and sedimentation precipitation method; The specific steps of the coprecipitation method are: Copper nitrate solution, nickel nitrate solution, silver nitrate solution and aluminum nitrate solution are prepared respectively, and according to the composition of the target catalyst, the copper nitrate solution, nickel nitrate solution, silver nitrate solution and aluminum nitrate solution are uniformly mixed, and sodium carbonate solution is added dropwise in an ice water bath to generate a precipitate, and the pH value of the reaction end point is controlled; aging; washing the precipitate with deionized water to neutrality; drying; roasting; grinding into powder, and reducing to obtain the copper-nickel-silver composite metal catalyst; The specific steps of the impregnation method are: Copper nitrate solution, nickel nitrate solution and silver nitrate solution are prepared respectively, and according to the composition of the target catalyst, the copper nitrate solution, nickel nitrate solution and silver nitrate solution are mixed evenly, and then γ-Al2O3 is added and mixed evenly; aging is performed to remove water from the reaction solution to obtain a solid; drying; roasting; grinding into powder, and reducing to obtain the copper-nickel-silver composite metal catalyst; The specific steps of the Galvanic replacement method are: Prepare copper nitrate solution, nickel nitrate solution and aluminum nitrate solution respectively, mix the copper nitrate solution, nickel nitrate solution and aluminum nitrate solution evenly according to the composition of the target catalyst, add sodium carbonate solution dropwise in an ice water bath to generate precipitation; control the pH at the reaction endpoint; Aging; washing the precipitate with deionized water until neutral; drying; Roasting; Grinding into powder, reducing, and obtaining a catalyst precursor; adding all of the obtained precursor into ethanol, preparing a silver nitrate solution, dripping the silver nitrate solution into the precursor, aging; washing to obtain a precipitate; and drying to obtain the copper-nickel-silver composite metal catalyst; The specific steps of the sedimentation precipitation method are: Prepare copper nitrate solution, nickel nitrate solution and silver nitrate solution respectively, mix the copper nitrate solution, nickel nitrate solution and silver nitrate solution evenly according to the composition of the target catalyst, and then add γ-Al2O3 and mix evenly; add sodium carbonate solution dropwise under ice bath condition to generate precipitation, and control the pH of the reaction end point; age; wash the precipitation with deionized water to neutrality; dry; calcining; grinding into powder, and reducing to obtain the copper-nickel-silver composite metal catalyst.
2. A method for preparing a copper-nickel-silver composite metal catalyst as claimed in claim 1, characterized in that: In the coprecipitation method, the molar concentrations of the copper nitrate solution and the nickel nitrate solution are 0.2-0.25 mol / L respectively; the molar concentration of the silver nitrate solution is 15-25 mmol / L; the molar concentration of the aluminum nitrate solution is 0.5-0.7 mol / L; the molar concentrations of the sodium carbonate solution are 0.8-2.0 mol / L respectively; and the volume ratio of the copper nitrate solution, the nickel nitrate solution, the silver nitrate solution, the aluminum nitrate solution and the sodium carbonate solution is 15-20:15-20:10-15:15-20:25-30.
3. A method for preparing a copper-nickel-silver composite metal catalyst as claimed in claim 1, characterized in that: In the coprecipitation method, the reaction end point pH is controlled to be 9-11; the aging is carried out for 3-5 hours; the precipitate is dried at 100-110° C. for 10-12 hours, calcined at 400-500° C. for 3-4 hours; and reduced at 350-500° C. for 2-3 hours at a hydrogen flow rate of 5 mL / min.
4. A method for preparing a copper-nickel-silver composite metal catalyst as claimed in claim 1, characterized in that: In the impregnation method, the molar concentrations of the copper nitrate solution and the nickel nitrate solution are 0.2-0.25 mol / L respectively; the molar concentration of the silver nitrate solution is 15-25 mmol / L; the masses of copper nitrate, nickel nitrate, silver nitrate and γ-Al2O3 in the copper nitrate solution, the nickel nitrate solution and the silver nitrate solution are 7.2480-12.10:8.7237-14.50:0.2548-0.6370:15-20.
5. A method for preparing a copper-nickel-silver composite metal catalyst as claimed in claim 1, characterized in that: In the impregnation method, the solid is aged at room temperature for 3-5 hours and the water is removed by rotary evaporation; the solid is dried at 100-110° C. for 10-12 hours, calcined at 400-500° C. for 3-4 hours, and reduced at 350-500° C. for 2-3 hours at a hydrogen flow rate of 5 mL / min.
6. A method for preparing a copper-nickel-silver composite metal catalyst as claimed in claim 1, characterized in that: In the Galvanic replacement method, the molar concentrations of the copper nitrate solution and the nickel nitrate solution are 0.2-0.25 mol / L, respectively; the molar concentration of the silver nitrate solution is 15-25 mmol / L; the molar concentration of the aluminum nitrate solution is 0.5-0.7 mol / L; the molar concentrations of the sodium carbonate solution are 0.8-2.0 mol / L, respectively; and the volume ratio of the copper nitrate solution, the nickel nitrate solution, the aluminum nitrate solution and the sodium carbonate solution is 15-20:15-20:15-20:25-30.
7. A method for preparing a copper-nickel-silver composite metal catalyst as claimed in claim 1, characterized in that: In the Galvanic replacement method, the reaction endpoint pH is controlled to be 9-11; the reaction is aged for 3-5 hours; the precipitate is dried at 100-110°C for 10-12 hours, and calcined at 400-500°C for 3-4 hours; the precipitate is reduced at 350-500°C for 2-3 hours at a hydrogen flow rate of 5 mL / min; a silver nitrate solution is added to the catalyst precursor, and the catalyst is aged at 35°C for 3-5 hours; the precipitate is washed by centrifugation with ethanol for 3 times to obtain a precipitate; and the precipitate is vacuum dried at 40°C for 8 hours.
8. A method for preparing a copper-nickel-silver composite metal catalyst as claimed in claim 1, characterized in that: In the deposition precipitation method, the molar concentrations of the copper nitrate solution and the nickel nitrate solution are 0.2-0.25 mol / L, respectively; the molar concentration of the silver nitrate solution is 15-25 mmol / L; the molar concentration of the sodium carbonate solution is 0.8-2.0 mol / L, respectively; the masses of copper nitrate, nickel nitrate, silver nitrate, sodium carbonate and γ-Al2O3 in the copper nitrate solution, the nickel nitrate solution, the silver nitrate solution and the sodium carbonate solution are 7.2480-12.10:8.7237-14.50:0.2548-0.6370:21.20-63.60:15-20; the reaction endpoint pH is controlled to be 9-11; the reaction is aged for 3-5 hours; the precipitate is dried at 100-110°C for 10-12 hours, and calcined at 400-500°C for 3-4 hours; and the precipitate is reduced at 350-500°C for 2-3 hours at a hydrogen flow rate of 5 mL / min.
9. A copper-nickel-silver composite metal catalyst, characterized in that: The catalyst is prepared by the preparation method described in any one of claims 1 to 8.
10. A method for using the copper-nickel-silver composite metal catalyst as claimed in claim 9, characterized in that: The catalyst is used for catalytic amination of ethylene glycol to prepare ethylenediamine and co-produce piperazine.
Citation Information
Patent Citations
Process for the distillative separation of mixtures comprising monoethylene glycol and diethylentriamine
CN101384542A
Catalyst for preparing ethylene diamine through amination of ethylene glycol and preparation method thereof
CN102233272A
Catalyst for synthesizing ethylene amine and method for preparing ethylene amine
CN102658162A
Cited By
Preparation method of cobalt-based catalyst and application of cobalt-based catalyst in ethylene glycol amination reaction
CN121016804A